2017
DOI: 10.17269/cjph.108.6105
|View full text |Cite|
|
Sign up to set email alerts
|

Migration and social determinants of mental health: Results from the Canadian Health Measures Survey

Abstract: OBJECTIVES: Studies worldwide point to increased risk of mental health problems among immigrants. However, the data on Canadian immigrants' mental health are ambiguous. To address this, we examined the relationship of both self-perceived mental health and reported diagnosis of mood disorders with age, gender, migration status, time since migration, and social determinants of health factors. METHODS:We analyzed three cycles of the Canadian Health Measures Survey. Our outcome variables were self-perceived mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 21 publications
7
36
1
1
Order By: Relevance
“…Our findings build on prior literature by presenting estimates of lifetime and twelve-month rates of specific mood, anxiety, and substance use disorders for foreign-born Caribbean women to better aid mental health services planning for this growing population. Consistent with studies of mental health and substance use among African and Caribbean immigrants carried out in other countries [ 54 , 55 , 56 , 57 ], we found Black women who have migrated from the Caribbean had lower rates of psychiatric disorders than Black women born in the U.S., especially for substance use disorders. These results are consistent with the healthy immigrant literature, which finds that foreign-born populations often have better health and mental health outcomes [ 13 , 16 , 54 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings build on prior literature by presenting estimates of lifetime and twelve-month rates of specific mood, anxiety, and substance use disorders for foreign-born Caribbean women to better aid mental health services planning for this growing population. Consistent with studies of mental health and substance use among African and Caribbean immigrants carried out in other countries [ 54 , 55 , 56 , 57 ], we found Black women who have migrated from the Caribbean had lower rates of psychiatric disorders than Black women born in the U.S., especially for substance use disorders. These results are consistent with the healthy immigrant literature, which finds that foreign-born populations often have better health and mental health outcomes [ 13 , 16 , 54 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with studies of mental health and substance use among African and Caribbean immigrants carried out in other countries [ 54 , 55 , 56 , 57 ], we found Black women who have migrated from the Caribbean had lower rates of psychiatric disorders than Black women born in the U.S., especially for substance use disorders. These results are consistent with the healthy immigrant literature, which finds that foreign-born populations often have better health and mental health outcomes [ 13 , 16 , 54 , 57 , 58 , 59 , 60 , 61 ]. In addition, this study contributes to the literature by demonstrating the chronic course of mental health and substance use disorders, such as dysthymia and panic disorder in African American women, which appear to persist even for women who have accessed mental health services during the lifetime.…”
Section: Discussionsupporting
confidence: 91%
“…It was already suggested that recent immigrants to Canada, who are usually highly educated [11], have on average comparable or sometimes better health outcomes than the native population [30]. Some authors describe a healthy immigrant effect in wealthy countries such as Australia, Canada, Europe and USA: recent immigrants have a better physical and mental health status than national born citizens [17,[31][32][33]. However, these health trends seem to deteriorate with years spent in the host country and over time migrant health statuses become closer to the native-born population, as has been observed in Canada and elsewhere [2,3,31].…”
Section: Introductionmentioning
confidence: 99%
“…The ‘right to health’ of migrants is enshrined in the Declaration of Alma-Ata (1978) and states receiving countries should take a comprehensive approach to healthcare of such sojourners beyond basic infectious disease control 5. Accordingly, migration is increasingly recognised as a structural socio-economic force that influences health outcomes as a social determinant of health, in general, and mental health, in particular 6 7…”
Section: Introductionmentioning
confidence: 99%